Production of disease-free planting material of Nagpur mandarin (Citrus reticulata) by shoot tip grafting - A.K. DAS and SHYAM SINGH, N. VIJAYAKUMARI*, D.K. GHOSH (Indian Phytopathology, 2006)
Shoot tip grafting (STG) has been standardized to produce true-to-type and virus-free planting material and subsequently to establish virus-free protected and field foundation blocks. Both biological and serological indexing were done for testing selected superior mother trees and STG-derived plants. A total of 245 STG grafts have been produced, of which 203 plants were found free from virus and virus-like diseases. These STG-derived disease-free plants were used to develop foundation block which acts as a source of virus-free scion material. So far 15,000 STG derived healthy citrus plants were produced and released to citrus growers and nursery men.